Full solid-state magnetic refrigeration device toward thermal management - Yuan Lin; Victorino Franco; Jing Wang; Jia Yan Law; Yunzhong Chen; Jirong Sun; Tongyun Zhao; Fengxia Hu; Baogen Shen (Proceedings of the National Academy of Sciences, 2026)
The demand for thermal management of electronics is rapidly increasing due to the prosperity of information technology. However, the two major alternatives, convective cooling and vapor compression technologies, have limitations for the effective refrigeration of microchips, namely the low convective heat-transfer coefficient of gas, and the need of large compressors, not to mention the low efficiency of compressor cooling and its use of greenhouse refrigerant. Herein, we establish a full solid-state magnetic refrigeration device with scalability and simple structure based on hybrid regeneration utilizing solid heat transfer materials, aiming at offering active point-to-point thermal management through solid-to-solid contact to targets with different footprints. Even with the intrinsic experimental imperfections of a laboratory demonstrator, the device shows a high heat-transfer coefficient h of 336 W m −2 K −1 (typically forced air convection by electric fans have <100 W m −2 K −1 ), a high unit cascade heat-transfer coefficient h / n of 168 W m −2 K −1 , and a large area cooling power W of 0.72 W cm −2 at the temperature difference between environment T e and hot object T o of −20 K, which make our full solid-state design the best in the field of thermal management compared to reported full solid-state caloric devices.